AB0561 Risk of HBV infection reactivation in patients with rheumatoid arthritis undergoing treatment with ANTI-CD20 (RITUXIMAB). (23rd January 2014) - Covelli, M.; Lanciano, E.; Notarnicola, A.; Coladonato, L.; Lopalco, G.; Scioscia, C.; Anelli, M.G.; Lapadula, G.
Abstract : Background: Hepatitis B virus reactivation is an emerging cause of liver disease in patients undergoing treatment with biologic agents. In particular, the risk of reactivation increases in anti-CD20 (Rituximab) and anti-TNF-alpha therapy. In patients affected by lymphoma and treated with Rituximab, HBV infection is the most common viral infection. In these patients several guidelines recommend strictly monitoring of ALT and serum HBV DNA. However other Authors recommend prophylactic therapy with antiviral agents and show that risk of reactivation is greatly reduced by the identification of high-risk patients and by using lamivudine. These guidelines are extended to patients affected by rheumatoid arthritis and treated with Rituximab. We've studied the risk of reactivation of Hepatitis B in our rheumatoid arthritis patients treated with Rituximab, refractory to one or more anti-TNF alpha blockers. Objectives: To evaluate risk of HBV infection reactivation in patients with rheumatoid arthritis undergoing treatment with ANTI-CD20 (RITUXIMAB). Methods: Occult HBV infection (HBsAg negative, anti-HBcAg positive with or without anti-HBsAg and undetectable HBV-DNA) has been observed in 218 patients; 16 of them were undergoing treatment with Rituximab from 2007 to 2010 without prophylactic therapy with antiviral agents. These patients received intravenous rituximab (mean 4 courses, consisting of 2 infusions of 1000 mg each separated by 2 week every 6 months). Results: In whole 16 patients HBV-DNA was negative before starting therapy and now it still remains undetectable. Finally there wasn't any increase of AST or ALT. Conclusions: Prophylactic therapy with antiviral agents is recommended in occult HBV infection patients treated with rituximab. However our patients undergoing rituximab not in combination with prophylactic therapy with lamivudine before 2010, didn't present reactivation of HBV infection. Therefore, according to data of our experience, Rituximab appears to be a safe treatment in patients with occult HBV infection too. Further studies are necessary to confirm our experience data. Disclosure of Interest: None Declared